1993
DOI: 10.1073/pnas.90.5.2087
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of nitric oxide signaling by interstitial cells isolated from canine colon.

Abstract: The effects of nitric oxide (NO) on intracel- collected by using a video-based imaging system that has been described (23). The locations of cells of interest were specified by using a computer mouse and custom-designed software. Signals were recorded as the fluorescence within a rectangular region over each cell. Fluorescent responses were normalized by dividing by the maximum response to the bath perfusion of a solution containing 1 ,uM Bay K 8644. Thus, the ratio associated with the ordinate of each trace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 27 publications
6
90
0
1
Order By: Relevance
“…Because NO synthesis by constitutive nitric oxide synthase (cNOS) is usually calcium-dependent (Moncada et al, 1991), a rise in [Ca 2ϩ ] i may serve to amplify NO production as previously reported (Publicover et al, 1993), and a high rate of potentially unrestricted diffusion for NO could also give rise or contribute to Ca 2ϩ waves seen in many single cells and tissues (Berridge and Dupont, 1994). Therefore, considering the presence of Ca 2ϩ -dependent nitric oxide synthase in glia (Feinstein et al, 1994) and the possibility of cross-talk between NO and Ca 2ϩ in these cells, this study investigated whether the NO-G-kinase signaling pathway is involved in Ca 2ϩ homeostasis in glia and whether a hypothetical mobilization of Ca 2ϩ by NO might initiate regenerative intercellular Ca 2ϩ waves or contribute to intercellular Ca 2ϩ wave propagation induced by mechanical stress of single glial cells in mixed glial-neuron cultures.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Because NO synthesis by constitutive nitric oxide synthase (cNOS) is usually calcium-dependent (Moncada et al, 1991), a rise in [Ca 2ϩ ] i may serve to amplify NO production as previously reported (Publicover et al, 1993), and a high rate of potentially unrestricted diffusion for NO could also give rise or contribute to Ca 2ϩ waves seen in many single cells and tissues (Berridge and Dupont, 1994). Therefore, considering the presence of Ca 2ϩ -dependent nitric oxide synthase in glia (Feinstein et al, 1994) and the possibility of cross-talk between NO and Ca 2ϩ in these cells, this study investigated whether the NO-G-kinase signaling pathway is involved in Ca 2ϩ homeostasis in glia and whether a hypothetical mobilization of Ca 2ϩ by NO might initiate regenerative intercellular Ca 2ϩ waves or contribute to intercellular Ca 2ϩ wave propagation induced by mechanical stress of single glial cells in mixed glial-neuron cultures.…”
mentioning
confidence: 95%
“…2b,d,e), underscoring a specific effect for NO on intracellular Ca 2ϩ release in glia. It has previously been reported that NO-induced Ca 2ϩ mobilization is ryanodine receptor (RyR)-linked in several cell types (Publicover et al, 1993;Willmott et al, 1995a;Willmott et al, 1996c). To test for the involvement of a RyR-mediated Ca 2ϩ release mechanism, cells were preincubated with an antagonizing concentration of ryanodine before NO application.…”
Section: Nitric Oxide Induces Ca 2؉ Mobilization In Glial Cells Via Tmentioning
confidence: 99%
See 2 more Smart Citations
“…6,[9][10][11] Recent morphological and functional evidence from various organs suggests that ICC and ICs might act as the primary targets for nerve-released NO to have a important role in NO-dependent signal transduction and smooth muscle relaxation. [12][13][14] ICs have been identified by their immunoreactivity to the kit receptor in the corporal tissue from man and several animals. [15][16][17] As dispersed corporal SMCs are able to generate spontaneous electrical activity by opening Ca 2 þ -activated Cl À channels, which is primarily initiated by spontaneous Ca 2 þ store-dependent membrane depolarization, 18,19 the role of ICs in corporal tissues as the primary electrical pacemaker has been questioned; they may serve as intermediaries in the transmission of nerve signals to SMCs or have other functional roles.…”
Section: Introductionmentioning
confidence: 99%